The Interfaith Relations in West Aceh: An Ethnographic Study and the Role of the Religious Harmony Forum (FKUB): Relasi Antarumat Beragama di Aceh Barat: Kajian Etnografi dan Peran Forum Kerukunan Umat Beragama (FKUB) - Fikriya Aniqa Fitri; Darlin Rizki; Nisa Ulmuftia (DIALEKTIKA, 2026)
This study aims to analyze the social relations between Muslims and non-Muslims in West Aceh and to examine the role of the Interfaith Harmony Forum (FKUB) in fostering religious harmony, tolerance, and character development within the community. This research employs a qualitative method with an ethnographic approach. It integrates a literature review, which serves as a reference source for moderation, with fieldwork conducted in West Aceh as the research site. One of the primary objectives of establishing FKUB in West Aceh is to promote and maintain interreligious harmony and to empower religious communities to develop sustainably. The role of FKUB in strengthening interfaith relations and contributing to societal character development is a shared responsibility of all citizens and governmental institutions. The scope of peace and order includes enhancing the achievement of religious harmony, coordinating activities among vertical institutions, strengthening mutual understanding, mutual respect, and tolerance among religious groups, as well as supporting the development of places of worship. In accordance with the mandate of FKUB in fostering community character, dialogue with religious leaders and community representatives is essential, taking into account the aspirations of various religious groups and society at large, and formulating these insights into actionable recommendations. Religious communities are expected to prioritize harmony. When religion is cultivated as a unifying force, it can contribute significantly to national stability and development. In carrying out their religious obligations, adherents must not interfere with or antagonize one another, and instead must uphold mutual respect. To create harmony in religious life, all believers should demonstrate mutual understanding, unity, cooperation, peace, and solidarity among members of society living together. The attainment of tranquility and interreligious harmony is crucial and beneficial across various aspects of life, ultimately fostering a community characterized by harmony, brotherhood, closeness, connectedness, kindness, and mutual respect.